HOMOSEKSUAL: ANALISIS HUKUM DAN NILAI MORAL DALAM ISLAM (STUDI MAWDLUI PERSPEKTIF TAFSIR IBNU KATSIR) - Joeha, Avif Alfiyah; Avif Alfiyah; Sugiarto, Fitrah; Nazila, Salwa Dama; Shofiyah, Shofiyah (MADINAH, 2025)
Homosexuality is a contemporary issue that sparks debate from legal, social, and ethical perspectives, particularly within the framework of Islamic teachings. This article explores the phenomenon using a thematic interpretation approach (tafsir mawḍūʿī), focusing on the exegesis of Ibn Kathir regarding relevant Qur’anic verses. Employing a qualitative method and content analysis technique, the study examines how Ibn Kathir interprets verses related to homosexual behavior. The findings indicate that Ibn Kathir views homosexuality as a moral deviation that contradicts human nature and Islamic law. His interpretation strongly affirms the prohibition of such behavior and highlights its negative consequences, both spiritually and socially. From the perspective of Islamic moral values, homosexuality violates principles of purity, dignity, and the ideal family structure. Ibn Kathir classifies it as a major sin (kabā’ir) and considers it a threat to the moral fabric of society. This study emphasizes that, according to Ibn Kathir, homosexuality not only breaches divine law but also undermines ethical norms and social order upheld in Islam. Thus, the research reinforces the Islamic legal stance on the prohibition of homosexuality and underlines the importance of preserving moral values and family integrity based on Islamic teachings.